Poor outcome of pediatric B-cell acute lymphoblastic leukemia associated with high level of CRLF2 gene expression in distinct molecular subtypes - Lin, Danna; Yang, Keyan; Yu, Lihua; Huang, Lulu; Lai, Xiaorong; Wu, Li; Xia, Xiayu; Zhang, Jingwen; Zheng, Qinlong; Yang, Lihua (Frontiers in Oncology, 2023)
Background: Overexpression of the cytokine receptor-like factor 2 (CRLF2) gene is the most common feature in the Philadelphia chromosome (Ph)-like subtype of B-cell acute lymphoblastic leukemia (B-ALL). However, the predictive value of CRLF2 overexpression for the prognosis of pediatric B-ALL patients remains controversial. The molecular mechanisms that upregulate CRLF2 expression level in patients has not been fully elucidated. Methods: In this study, the prognostic impact of CRLF2 expression level on molecular types of B-ALL in pediatric patients from Zhujiang Hospital (n = 111) was retrospectively analyzed. Youden index analysis was used to categorize CRLF2 expression into 3 groups, and these categories more precisely described the differences in the prognosis of patients with varying expression levels of CRLF2 in both the Zhujiang Hospital cohort and the TARGET cohort. Results: We used the Zhujiang Hospital cohort as a discovery cohort to determine the cutoff value of CRLF2 expression. CRLF2-high patients accounted for approximately 6%. In addition, the percentage of bone marrow blast cells and initial white blood cell count in CRLF2-high patients were higher than those in CRLF2-low patients, and MRD turned negative slower. The results were validated in the TARGET cohort and indicated that CRLF2 overexpression could be subdivided by CRLF2 expression levels into 2 categories: CRLF2-high with a poor survival and CRLF2-medium with a good OS and EFS. Such heterogeneity was attributed to the different molecular mechanisms leading to CLRF2 upregulation, where the CRLF2 overexpression level was high in Ph-like B-ALL and medium in high hyperdiploid B-ALL. Conclusion: This study highlights the importance of the molecular mechanisms of the upregulation of CRLF2 expression in predicting the prognosis of pediatric B-ALL patients.